Electrolytes Profile of Estrual Mucus of Gir Cows with Reference to Body Condition Score and Fertility - Gohel, Mukesh M; Kavani, Fulabhai S; Dhami, Arjun J; Hadiya, Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Fifty Gir cows of different reproductive status (10 = normal cyclic, 20 = repeat breeders and 20=induced estrus) were selected to determine  the association of electrolytes mainly the macro-minerals profile of their estrual cervico-vaginal mucus (CVM) to their body condition  score (BCS) and fertility post-AI. The overall pooled mean concentrations of calcium, inorganic phosphorus, magnesium, sodium and  potassium obtained in CVM of Gir cows were 14.27 ± 0.33 mg/dL, 1.87 ± 0.13 mg/dL, 4.24 ± 0.10 mEq/L, 159.85 ± 5.52 mEq/L and  29.50 ± 0.78 mEq/L, respectively. The repeat breeding cows had significantly (p
Keywords: BCS; Estrual cervical mucus; Fertility; Gir cows; Macro-minerals profile